2006
DOI: 10.1152/japplphysiol.00166.2006
|View full text |Cite
|
Sign up to set email alerts
|

Castration prevents suppression of MHC class II (Ia) expression on macrophages after trauma-hemorrhage

Abstract: . Castration prevents suppression of MHC class II (Ia) expression on macrophages after trauma-hemorrhage. J Appl Physiol 101: 448 -453, 2006. First published April 13, 2006; doi:10.1152 doi:10. /japplphysiol.00166.2006eral studies indicate that cell-mediated immune responses, i.e., macrophage (M⌽) cytokine release capacities, myosin heavy chain (MHC) class II (Ia) expression, etc., are suppressed after traumahemorrhage in male mice. Testosterone has been shown to be responsible for the depression of M⌽ cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
(68 reference statements)
1
12
0
Order By: Relevance
“…This matches the clinical experience in that patients are at high risk of immune suppression and subsequent infection even though their major injury has been successfully treated. 57 In addition to the well known fact that posttraumatic suppression of adaptive immunity is due to reduced major histocompatability complex II expression and impaired antigen presentation, 8,58,59 our current study indicated that dysregulation of T-cell costimulatory signaling may also play a crucial role in the induction of T-cell anergy after trauma-hemorrhage.…”
Section: Discussionmentioning
confidence: 54%
“…This matches the clinical experience in that patients are at high risk of immune suppression and subsequent infection even though their major injury has been successfully treated. 57 In addition to the well known fact that posttraumatic suppression of adaptive immunity is due to reduced major histocompatability complex II expression and impaired antigen presentation, 8,58,59 our current study indicated that dysregulation of T-cell costimulatory signaling may also play a crucial role in the induction of T-cell anergy after trauma-hemorrhage.…”
Section: Discussionmentioning
confidence: 54%
“…Similarly, a significant decrease in the release of the proinflammatory cytokines IL-1β and IL-6 by splenic macrophages and peritoneal macrophages was observed in DHT-treated castrated male mice following trauma-hemorrhage (91). MHC class II expression was also shown to be decreased in peritoneal and splenic macrophages after trauma-hemorrhage (92). Estrogens have been shown to increase the resistance of host animals to infections and also stimulate macrophage functions, suggesting that female sex steroids should improve macrophage function in contrast to the immunodepressive effects of male sex steroids (93)(94)(95).…”
Section: Macrophages and Dendritic Cellsmentioning
confidence: 77%
“…41 Mayr and others reported that major histocompatibility class II expression by macrophages in male mice was suppressed after traumainduced hemorrhage, and that this suppression was prevented by castration. 42 In male mice, these alterations in immune function, which may be caused by the lack of testosterone after orchidectomy, might control parasitemia increases and aggravation of anemia in infected orchidectomized mice.…”
Section: Discussionmentioning
confidence: 99%